2014
DOI: 10.1111/jcpe.12276
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the bone dimension following immediate implant placement into extraction socket: systematic review and meta‐analysis

Abstract: The bone dimensions of immediate implant sites demonstrated approximately 0.5-1.0 mm reduction in vertical and horizontal aspects 4-12 months following surgery. The results should be interpreted with care because of the data heterogeneity. The correlation of the socket buccal wall thickness, and other variables, with dimensional changes of the bony ridge should be investigated further in controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 54 publications
(77 reference statements)
8
61
0
Order By: Relevance
“…With reference to this topic, our SR showed interesting results: after immediate implant insertion alone, on the buccal side, alveolar ridges underwent a horizontal and vertical reduction that was on average 1 mm; these results are in accordance with those from a very recent SR (Lee et al. ) analysing bone dimensional changes after immediate implant placement and reporting approximately 0.5 – 1.0 mm reduction in vertical and horizontal aspects after 4 – 12 months following surgery. These data revealed a slight lower mean reduction from those reported by other SR after spontaneous healing (Van der Weijden et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With reference to this topic, our SR showed interesting results: after immediate implant insertion alone, on the buccal side, alveolar ridges underwent a horizontal and vertical reduction that was on average 1 mm; these results are in accordance with those from a very recent SR (Lee et al. ) analysing bone dimensional changes after immediate implant placement and reporting approximately 0.5 – 1.0 mm reduction in vertical and horizontal aspects after 4 – 12 months following surgery. These data revealed a slight lower mean reduction from those reported by other SR after spontaneous healing (Van der Weijden et al.…”
Section: Discussionsupporting
confidence: 89%
“…So, conversely to Lee et al. (), in our SR study groups were stratified by the type of regenerative technique, using a graft or a barrier alone or a combination of both. Also, data were stratified by study design (RCTs and cohort studies) and evaluation method (clinical and tridimensional radiography).…”
Section: Discussionmentioning
confidence: 96%
“…Immediate implantation, despite numerous benefits, does not preclude loss of the buccal bone, 1 , 2 gingival recession (GR), 3 or ridge dimensional change 4 , 5 . Bone grafts, barriers, and soft tissue grafting have been used separately or together to minimize gingival and ridge contour changes after immediate implantation.…”
mentioning
confidence: 99%
“…A number of clinical reports on immediate placement have been published since then [39][40][41], and it was demonstrated that bone resorption cannot be prevented completely by immediate placement. The results of a systematic review regarding alterations of the bone dimensions following immediate implant placement into an extraction socket by Lee et al showed that the median amount of buccal bone resorption at 4-12 months after immediate placement was 1.07 mm horizontally and 0.78 mm vertically [42]. The weighted mean palatal bone dimensional reduction was 0.62 mm horizontally and 0.50 mm vertically.…”
Section: Immediate or Early Implant Placementmentioning
confidence: 97%